EFEKTIVITAS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN AKHLAK MULIA SISWA DI SEKOLAH MENENGAH PERTAMA: KAJIAN PUSTAKA - Muhammad Arsyad; Abdul Rahman (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2026)
This article aims to analyse the effectiveness of Islamic Religious Education in fostering noble character among junior secondary school pupils through a literature review. Islamic Religious Education plays a vital role in shaping pupils’ character, morals and behaviour, particularly during early adolescence—a phase in which they are vulnerable to the influence of their social environment and the development of digital technology. This study is based on the finding that the implementation of Islamic Religious Education (IRE) integrated with religious practices, exemplary teacher behaviour, and a conducive school culture has a positive impact on the development of students’ discipline, responsibility, good manners, and social awareness. The results of the study indicate that the effectiveness of Islamic Religious Education is influenced by the teaching strategies employed by teachers, students’ levels of motivation and awareness, family support, the school environment, as well as the influence of social media and peer groups. The strategies most frequently assessed as effective include setting a good example, fostering religious habits, offering guidance, reinforcing religious culture, and integrating moral values into daily learning activities. Consequently, Islamic Religious Education (IRE) should not merely emphasise cognitive aspects but must be directed towards the internalisation of values and the development of tangible behaviour in order to sustainably enhance students’ noble moral character.